2020
DOI: 10.21776/ub.jam.2020.018.02.20
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Work Stress on Turnover Intention: Employee Performance as Mediator in Casual-Dining Restaurant

Abstract: The purpose of this study was to examine the effect of work stress on employee performance, the effect of employee performance on turnover intentions, work stress on turnover intentions, and examine the indirect effect of work stress on turnover intentions through employee performance as mediation. This research was conducted on employees of casual-dining restaurants in the city of Malang, East Java. The analysis model uses Partial Least Square. The results showed that work stress has a significant negative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
9
1
1
Order By: Relevance
“…Thus, the greater the job stress employees endure, the greater the likelihood of turnover. The finding contradicts previous research [7], [8], and [9], which indicate that job stress does not affect employee turnover intention.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, the greater the job stress employees endure, the greater the likelihood of turnover. The finding contradicts previous research [7], [8], and [9], which indicate that job stress does not affect employee turnover intention.…”
Section: Resultscontrasting
confidence: 99%
“…According to research [1], [2], [3], [4], [5], and [6], work stress has a beneficial effect on intention to leave. While work stress does not have a significant effect on the intention to leave, as demonstrated by [7], [8], and [9]. Along with job stress, compensation is another factor that influences turnover intention.…”
Section: Introductionmentioning
confidence: 92%
“…The results of this study are also affected by worsening economic factors due to the covid-19 pandemic, where employees themselves feel that work stress does not affect their desire to quit because they need this job so that mediating job satisfaction also does not affect their desire to quit in terms of work stress. Partially, in the study (Suswati, 2020) it was found that the effect of work stress on turnover intention was not significant. The result is consistent with study that is conducted on employees of working in a Bank, it was found that partially work stress did not affect job satisfaction and turnover intention (Ramlawati et al, 2021).…”
Section: Hypothesismentioning
confidence: 84%
“…Although work stress has been demonstrated as a robust predictor of the turnover intentions of health workers in previous studies [ 25 , 26 , 27 ], the relationship between work stress and turnover intention in other occupations or workers in other industries is still controversial [ 5 , 6 , 28 , 29 ]. Thus, the relationship between work stress and turnover intention need to be analyzed by utilizing data from surveys targeting employees working in all industries rather than a specific occupation/industry.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In other words, it is important to ensure that managers do not leave their organization by developing their careers and fully utilizing their capabilities to grow in their organization. From this point of view, it appears that work stress has a negative effect on career orientation [ 4 ], performance [ 5 ], and turnover intention [ 6 ], raising the need to pay attention to the stress that managers face in the workplace. This means the relationship between work stress, capabilities, career development behavior, and turnover intention should be comprehensively analyzed under recent career contexts where stress at work is increasing.…”
Section: Introductionmentioning
confidence: 99%